Działania krajów Unii Europejskiej w dziedzinie ochrony wód przed zanieczyszczeniem związkami azotu pochodzącymi z rolnictwa - Sobolewska, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
In many cases, the nitrate concentration in the most ground and surface waters of the EU countries exceeds the guideline value, and the maximum acceptable concentration of nitrate, in drinking water. One of the most important sources of nitrate pollution is agriculture. The European Commission issued some directives and regulations, which have direct or indirect influence on the reduction of po Il uti on caused by nitrates from the agricultural sources. The most important are the Council Directive 91/676/EEC and the Regulation (EEC) No 2078/92. A recent report on the implementation of the directive concluded that the status of its implementation in most Member States is unsatisfactory. So far, only five countries: Austria, Germiany, Denmark, Luxembourg and Sweden have submitted the required action programmes. All Member States have developed and implemented some agri-environmental programmes (consistent with the Regulation (EEC) No 2078/92). However, remarkable differences in their concept and execution between the Member States can be observed (for instance in Finland some of 87% of utilised agricultural area is covered by these programmes while in Greece merely about 0,6% respectively).